Strategi Implementasi dan Pengembangan: Studi Kasus MTS Surya Buana Malang - Adisty Zulfah Rizki Irani; Hanifia Izzah Rahmadanty; Thohirotul Ainiyah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study was conducted to address the research gap related to the lack of studies on the implementation and development of the 3R (Religious, Reasoning, Research) approach-based curriculum at the Madrasah Tsanawiyah level. Previous studies have focused more on the Merdeka Curriculum in public schools, so research is needed to describe the practice of contextual curricula in madrasahs, particularly the 3R model, which integrates religious values, literacy, and critical thinking skills. This study aims to explain the process of implementing the 3R curriculum at MTs Surya Buana Malang and to identify the supporting and inhibiting factors. The research method used is descriptive qualitative through participant observation, semi-structured interviews, and documentation. The informants consist of the Deputy Head of Curriculum as the key informant and several teachers as supporting informants. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion verification, with validation through source and technique triangulation. The results of the study show that the 3R program is integrated into school culture through religious activities, literacy, and research-based projects, thereby improving students' spiritual character, reasoning abilities, and research skills. The main supporting factors include madrasah leadership and teacher collaboration, while obstacles include limited practice facilities and research support tools. Overall, the 3R curriculum has proven effective in improving the quality of learning and is relevant for development in other madrasah